Insights into EFL Students' Reading Obstacles: A Qualitative Case Study - Holandyah, Muhamad; Marzulina, Lenny; Erlina, Dian; Herizal, Herizal; Putri, Hikmah Zalifah; Alfaridzi, Hanif (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
This study utilized qualitative research with a case study design to investigate the difficulties encountered by EFL students in reading comprehension. Nine students from Madrasah Aliyah Negeri 1 (State Islamic Senior High School) Muara Enim in South Sumatra who met the research sampling criteria were selected using the purposeful sampling technique. Data were collected through interviews, and the results were analyzed using thematic analysis. The findings revealed that the majority of students experienced obstacles in reading comprehension, including a lack of vocabulary, a limited grasp of grammar, unfamiliarity with the topic content, an inability to employ reading strategies effectively, and unappealing reading materials. This exploration of specific obstacles that EFL students encounter in reading comprehension could serve as the foundation for the development of targeted strategies and interventions aimed at supporting the students in improving their reading skills.